Chairman's report: African Elephant Specialist Group/Rapport de la presidente: Groupe des specialistes des elephants africains - Holly Dublin (Pachyderm)
Outlines the establishment of the CITES system for monitoring the illegal killing of elephants (MIKE) including the thus far nominated sites for its implementation, notes the setting of the terms of reference for AfESG itself as well as those of the Data Review Task Force and the Human-Elephant Conflict Task Force (HEFT). Reviews ongoing work on the Elephant Trade Information System (ETIS), and TRAFFIC'c Bad Ivory Database System (BIDS). Mentions the AfESG meeting held in Burkina Faso in January 1998 (the papers from this meeting comprise the bulk of this Issue of Pachyderm) as well as upcoming meetings and and ongoing involvement with others involved in elephant research and management.